Bromate in Bottled Water ‑ Potential Hazard for Human Health - Winid, Bogumiła (Geomatics and Environmental Engineering, 2019)
In the International Agency for Research on Cancer (IARC) classification, bromates (by-products of water treatment) are categorized as Class 2B carcinogens; i.e., substances that are possibly carcinogenic to humans. The maximal concentration of bromate in drinking water must not be higher than 10 Î¼g/L, while the WHO recommends that bromate levels should be as low as possible. Investigations undertaken in several countries have revealed the presence of bromate in bottled water, too. The main factor responsible for the presence of bromate is ozonation during the manufacturing process or bromate-contaminated substances used in the water disinfection. The regulations currently in force in Poland forbid the addition of bacteriostatic agents and the application of treatment processes that alter the microflora in water. On the other hand, raw water can be filtered, aerated, or treated with air enriched in ozone ‑ although only in the amounts required to remove iron, manganese, arsenic compounds, and sulfides. However, during the manufacturing process, bottled water may be exposed to ozone from electric-powered ionizers used in the process of the dry-cleaning of bottles or PET preforms. The maximal admissible bromate contents in bottled water is 3 Î¼g/L. The current regulations in Poland effectively reduce hazards due to the presence of bromate in water. However, the results of investigations undertaken in other countries indicate that this aspect should be brought to the attention of both water manufacturers and regulatory bodies.